2007
DOI: 10.1044/0161-1461(2007/018)
|View full text |Cite
|
Sign up to set email alerts
|

Development of the Literacy Achievement Gap: A Longitudinal Study of Kindergarten Through Third Grade

Abstract: The results of this study stress the need for speech-language pathologists to assess emergent literacy skills in their speech and language clients and to include appropriate literacy goals in the treatment regimen as a means for reducing the potential need for identification as learning disabled in reading in the later years of elementary school.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
42
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(50 citation statements)
references
References 30 publications
4
42
0
3
Order By: Relevance
“…That is, a potential way to reduce science achievement gaps may be by implementing policies providing children at risk with greater opportunities to learn about the natural and social sciences prior to or immediately following school entry, including by providing their parents with training in how to more effectively increase the children's readiness for schooling and/or through programs and policies that provide the children with greater access to informal learning opportunities, as often provided through high-quality child care and preschool. Substantial attention has already been focused on the need for such early childhood programs (e.g., Head Start, Early Reading First) to address emergent literacy and numeracy gaps during this early time period, as these gaps have been repeatedly established as highly predictive of later reading and mathematics achievement gaps (e.g., Chatterji, 2006;Downey, von Hippel, & Broh, 2004;Foster & Miller, 2007;Jordan, Kaplan, Ramineni, & Locuniak, 2009). Yet little attention has been given to the need to also address science achievement gaps during the preschool or early-elementary time periods (Tate et al, 2012).…”
Section: Study's Contributions and Implicationsmentioning
confidence: 99%
“…That is, a potential way to reduce science achievement gaps may be by implementing policies providing children at risk with greater opportunities to learn about the natural and social sciences prior to or immediately following school entry, including by providing their parents with training in how to more effectively increase the children's readiness for schooling and/or through programs and policies that provide the children with greater access to informal learning opportunities, as often provided through high-quality child care and preschool. Substantial attention has already been focused on the need for such early childhood programs (e.g., Head Start, Early Reading First) to address emergent literacy and numeracy gaps during this early time period, as these gaps have been repeatedly established as highly predictive of later reading and mathematics achievement gaps (e.g., Chatterji, 2006;Downey, von Hippel, & Broh, 2004;Foster & Miller, 2007;Jordan, Kaplan, Ramineni, & Locuniak, 2009). Yet little attention has been given to the need to also address science achievement gaps during the preschool or early-elementary time periods (Tate et al, 2012).…”
Section: Study's Contributions and Implicationsmentioning
confidence: 99%
“…Social and racial differences can impact children's language and literacy skills [35][36][37][38]. Low-income African children had less developed emergent literacy skills relative to their white peers [38].…”
Section: Introductionmentioning
confidence: 99%
“…It has also been found that students' initial reading skills predict their achievement as they progress in their elementary school years. Students who begin their primary education with stronger reading skills remain ahead of their peers who start with weaker skills (Cunningham & Stanovich, 1997;Denton, West, & Walston, 2003;Foster & Miller, 2007;Stanovich, 1986;Storch & Whitehurst, 2002;Whitehurst & Lonigan, 2001). Additionally, older students, compared to younger ones, are more likely to perform better on reading tests in early grades (Stipek & Byler, 2001;West, Denton, & Germino-Hausken, 2000;Zill & West, 2001).…”
Section: Introductionmentioning
confidence: 99%